El principio de favorabilidad en los deudores de créditos hipotecarios en la Legislación Ecuatoriana - Lopez Minta, Byron Marcelo (2023)
When talking about mortgage loans, it is established that they are money loans of amounts that exceed a very high item, amounts granted by financial entities such as Banks or Cooperatives; These credits can be accessed by natural persons, the same ones who are seeking to make credits in order to be able to buy some real estate or build within it, as well as for the remodeling of some real estate, among other aspects that are considered to be able to acquire these loans. However, in order to access these loans, mortgage debtors, as people who have the opportunity to obtain these loans are known in these cases, must put their real estate as collateral, for example, when wanting to take out a loan to build a house, the mortgage debtor in order to be given the loan must mortgage his land, in order to be able to acquire the loan and in turn the financial entity guarantees with that mortgaged asset the payment by the same debtor, which in case of non-compliance with the payment will make the forced sale of that real estate in order to recover the money that the financial entity lent to the debtor, thus leaving the debtor clearly economically disabled and at the same time without having the right to a home. The problem of this research is to analyze if the principle of favorability is applied for the benefit of mortgage debtors, so that they have decent housing or if these rights are violated.